Reorientasi Manajemen Pendidikan Pesantren - Rahman, Kholilur (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
This paper departs from the government's appreciation of some of the success of boarding school education. The authenticity and uniqueness of the pesantren cottage in addition to the treasures of the nation's cultural tradition is also a pillar supporting force of education to bring up the leaders of a moral nation. It is this reality that demands the management of educational institutions according to the demands of the times. The kiai's charismatic leadership in pesantren tends to embrace a centralized management system, and the implications of educational reforms encourage the emergence of formal education institutions that embrace a decentralized management system. The dichotomy of the two management systems demands a strategic step by applying a new, solutive model of leadership. A solution of the leadership model by developing a democratic leadership, ie leadership that appreciates the potential, ideas and work of all parties, both kiai as the leader of the santri as a guided individual. This requires a re-orientation of the pesantren education management system. In short, the implementation of education management in boarding school needs to be re-orientation of the lofty ideals of boarding school. Reorientation of pesantren boarding school management that is urgent to undertake, among others: leadership management and, initial management. Nevertheless, this reorientation must still be grounded in the concept of "al-muhÃƒÂ¢fadzatu 'al-al-qadÃƒÂ®mi al-shÃ„Âlih wa al-akhdu bi al-jadÃƒÂ®di al-ashlah" (preserving a good old culture, and engaging constructive and prospective new ideas)